Application of Human Resource Management Science in Malls Public Services in Sidoarjo: Penerapan Ilmu Manajemen Sumber Daya Manusia Pada Mall Pelayanan Publik Di Sidoarjo - Lusi Rahmawati; Amirah Najchan Hibah; Agustina Santi; Dewi Komala Sari (International Consortium of Education and Culture Research Studies, 2024)
General Background Bureaucratic reform requires modern public service integration to overcome complex administration and slow processing times. Specific Background The Public Service Mall in Sidoarjo consolidates government and private sector amenities, yet faces high urbanization demands requiring adaptive personnel administration. Knowledge Gap Previous literature predominantly examines traditional government institutions, leaving a structural deficit in understanding personnel adaptation and performance models specifically within integrated public service centers. Aims This research evaluates the application of personnel administration sciences to identify operational barriers and formulate strategic development solutions within the Sidoarjo facility. Results Qualitative field observations and interviews reveal significant operational progress alongside major constraints, primarily personnel limitations, lack of skilled professionalism, and restricted budgets. To overcome these barriers, management applies structural solutions including continuous education, rigorous recruitment, and targeted incentive programs to optimize employee motivation. Novelty This study provides a contextualized administrative framework specifically designed for the unique integrated operational structure of regional public service malls. Implications Developing adaptive personnel strategies and training protocols guarantees responsive public administration, fundamentally securing long-term service quality and community satisfaction. Highlights: Integrated public service centers face significant operational constraints primarily due to personnel limitations and restricted facility budgets. Strategic personnel development requires continuous education, rigorous recruitment, and targeted incentive systems to optimize administrative operations. Adaptive personnel management fundamentally secures community satisfaction by overcoming traditional bureaucratic delays and unresponsive administration. Keywords: Human Resource Management, Public Service Mall, Personnel Administration, Operational Challenges, Service Quality